Revisiting community-driven reconstruction in fragile states - Cyrus Samii (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2023)
Community-driven reconstruction (CDR) is an approach to post-war reconstruction that gives discretion to local community councils in establishing priorities and overseeing the implementation of reconstruction and development activities. A series of methodologically exceptional studies has raised questions about whether CDR generates any meaningful impact beyond the short run, given that desired effects on social cohesion and collective action capacity have not been realized. This paper argues that such analyses either underplay or miss entirely three extraordinary successes of CDR. CDR has stood out relative to alternative strategies in terms of its efficiency and relative invulnerability to corruption. Institutions created through CDR initiatives have endured in contexts in which other governance institutions have collapsed. CDR institutions have shown themselves to be adaptable to new service delivery needs that go beyond the original purpose of infrastructure delivery. Based on this evidence, CDR is an example of institutional engineering done right, and remains a highly appealing strategy for reconstruction and longer-term development in war-affected contexts.
Keywords: H7; N4; O21; 330; community-driven reconstruction; collective action; corruption; governance; infrastructure